Analisis Hukum Ekonomi Syariah tentang Implementasi Akad Qardh - Titi Martini; Resi Atna Sari Siregar; Nurmayani Pasaribu (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
The people of Tangga Bosi II have a habit of lending money, accompanied by the condition that the lender controls the rice fields. On the one hand, this is considered something reasonable, but on the other hand, this needs further investigation in a review of sharia economic law. In this regard, this study aims to describe the conditions of the Qardh contract that have been implemented in the village of Tanga Bosi II and to analyze these conditions in a review of sharia economic law analysis. The research method used is qualitative with a case study approach. Data collection techniques using observation, interviews, and documentation studies. The primary sources in this study are qardh actors in the village of Tangga Bosi II and related people. In contrast, the secondary data sources are obtained from books related to the author's thesis. The results of the study revealed that the qardh contract carried out by the Tanggga Bosi II village community was still based on oral, and it was customary based on agreement and trust intending to help each other or help each other, by way of the lender providing guarantees for his debt in the form of rice fields. A review of sharia economic law on the problems mentioned above includes injustice to the borrower because it is unfair to the borrower; other than that, he owes the rice fields for his livelihood to be controlled by the lender.